Cardiovascular And Etectrocardiographic Effects Of Lidocaine And Mepivacaine With And Without Adrenaline Using Mandibular Nerve Block Anesthesia Technique In Healthy Volunteers - Rodríguez Alfaro, Miguel (2009)
The objective of the present study was to evaluate and compare the effect of Iidocaine and mepivacaine alone and associated with epinephrine on the cardiovascular and electrocardiographic parameters,60 healthy volunteers were assigned in 4 groups: A (2% lidocaine), B (2% lidocaine with epinephrine 1: 100,000); C (3% mepivacaine), D (mepivacaine 2% with epinephrine 1: 100,000). Therefore of assigned, it was injected ldental cartridge of correspondent anesthetic to each volunteer, using the nerve block anesthesia technique for the inferior mandibular nerve. In each patient was performed the measure of the heart rate, blood pressure and electrocardiogram. These measurements were carried out 5 minutes before and then 15 after minutes the administration of local anesthetic. The participants of the lidocaine 2% without vasoconstrictor group showed decline in the indicator heart rate (p <0.05); while the mepivacaine 3% without vasoconstrictor group showed increase in the PR interval (p <0.05), and decrease in the QTc interval. The use of local anesthetics with vasoconstrictor produced no alteration in any of the evaluated parameters. The use of adrenaline asswiated a lidocaine and mepivacaine does nat modify the cardiovascular and electrocardiographic evaluated parameters, while the use of anesthetic without vasoconstrictor significantly altered any parameters but without clinical impact on patients.